Sintesis Gliserol Stearat Dari Gliserol Produk Industri Minyak Kelapa Sawit Untuk Proses Inhibitor Korosi - Wijaya, Ariyanto Hadi; Aznury, Martha; Dewi, Erwana (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
This study aims to synthesize glycerol stearate from palm oil industrial products and test its effectiveness as a corrosion inhibitor on aluminum metal. The synthesis was carried out through an esterification reaction between glycerol and stearic acid using a sulfuric acid catalyst at a temperature of 120°C with a reaction time variation of 120–220 minutes. The synthesized products were characterized using Thin Layer Chromatography (TLC) and Gas Chromatography–Mass Spectrometry (GC-MS) methods. The inhibitor effectiveness test was carried out using a gravimetric method based on the ASTM G31-21 standard in 1 M HCl solution. The results showed an optimum reaction time of 180 minutes with a yield of glycerol monostearate of 16.36%. TLC showed the highest Rf value close to the glycerol monostearate standard, while GC-MS detected the main compounds in the form of glycerol monopalmitate and glycerol monostearate. Effectiveness testing showed that the coating method produced an inhibition efficiency of 76.89%, higher than the direct mixing method of 73.69%. These results indicate that glycerol stearate has the potential to be an effective and environmentally friendly corrosion inhibitor based on biodiesel waste.